Curriculum Management in Pesantren-Based Excellence Schools for Achieving School Effectiveness: A Study of SMA Darul Ulum 2 Unggulan BPPT (Badan Pengkajian dan Penerapan Teknologi) Jombang - Fanani, Moh. Zainal; Mulyadi, Mulyadi; Padil, Padil (Scidac Plus, 2026)
This study examines curriculum management in pesantren-based excellence schools and its contribution to school effectiveness. It aims to analyze how curriculum planning, implementation, and evaluation are managed integratively within the educational ecosystem of SMA Darul Ulum 2 Unggulan BPPT Jombang. The research employs a qualitative case study approach. Data were collected through participatory observation, in-depth interviews, and document analysis involving school leaders, teachers, dormitory mentors, and curriculum administrators. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings show that curriculum management operates through three interconnected processes: purpose-driven curriculum planning, integrated implementation within the boarding school ecosystem, and multidimensional evaluation through the PPEPP quality assurance cycle. Curriculum planning combines the national curriculum, pesantren curriculum, and flagship programs, including Qur’anic memorization, scientific research mentoring, and academic achievement coaching. Curriculum implementation extends beyond classroom instruction by integrating learning, dormitory mentoring, and religious routines that function as a hidden curriculum shaping students’ discipline and moral commitment. Curriculum evaluation is conducted continuously through the monitoring of academic achievement, religious competence, and character development. Based on these findings, the study proposes the Pesantren-Based Integrated Curriculum Effectiveness Model (PICEM), which explains that school effectiveness emerges from the synergy between integrated planning, pesantren culture, boarding school learning, and continuous quality assurance.